2011
DOI: 10.1063/1.3582616
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a time-dependent structural phase transition in potassium sodium bismuth titanate

Abstract: High-energy synchrotron diffraction has been employed to demonstrate a time-dependent structural phase transition in 0.2K1/2Bi1/2TiO3–0.8Na1/2Bi1/2TiO3. It is demonstrated that the rapid increase in electric field (≥0.25 kV mm−1 s−1) induces a transformation from rhombohedral to mixed phase rhombohedral and tetragonal symmetry. When the electric field is applied slowly (<0.25 kV mm−1 s−1), no transformation occurs, and rhombohedral symmetry is maintained. The extent of transformation increases with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…The origin of the large electromechanical response of incipient piezoelectrics is generally attributed to an electric field induced phase transition. [140][141][142][143][144][145][146][147] Figure 2.14 at point displays an ergodic relaxor state, as previously discussed. For BNT-based lead-free incipient piezoelectrics, it was demonstrated that the electric field induced phase transition coincides with the inflection point of the strain output 148 and the transformation is followed by switching of the newly created domains.…”
Section: Lead-free Relaxor Ferroelectricsmentioning
confidence: 61%
See 4 more Smart Citations
“…The origin of the large electromechanical response of incipient piezoelectrics is generally attributed to an electric field induced phase transition. [140][141][142][143][144][145][146][147] Figure 2.14 at point displays an ergodic relaxor state, as previously discussed. For BNT-based lead-free incipient piezoelectrics, it was demonstrated that the electric field induced phase transition coincides with the inflection point of the strain output 148 and the transformation is followed by switching of the newly created domains.…”
Section: Lead-free Relaxor Ferroelectricsmentioning
confidence: 61%
“…Discrepancies are inherent to the change in probing frequencies of the different characterization techniques employed. 143,144 It is noted that the removal of the electric field leads to a decay of 65 % in the polarization of BNT-0.25ST, indicating that although in BNT-0.25ST is higher than in BNT-0.28ST, it still has considerably lower values than its . Domain switching is a time-dependent kinetic process 73,[441][442][443] , while a first order phase transition is an infinitely fast discontinuous process occurring in the terahertz range.…”
Section: Quasi-static Large Signal Propertiesmentioning
confidence: 97%
See 3 more Smart Citations